Work and settlement locations of immigrants: How are they connected? The case of the Oporto Metropolitan Area - Emília Malcata Rebelo (2012)
The research reported in this article aims to explain the residential and work location of different groups of immigrants living in a particular metropolitan area, based on the following underlying causes: socio-spatial differentiation resulting from the characteristics of urban economies, the performance of housing and labour markets, spatial and socioeconomic/professional mobility, and immigrants own characteristics. Within this scope, census data are analysed and cartographically displayed, and classification trees are applied in order to understand the relationship between the residential and work locations of the different population groups and their respective demographic, economic and professional characteristics, on the one hand, and land occupation densities, on the other. Although this methodology is applied to the Oporto Metropolitan Area (Portugal), it can easily be used in other urban and metropolitan areas.